New structural insights into anomeric carbohydrate recognition by frutalin: an α-d-galactose-binding lectin from breadfruit seeds - Vieira Neto, Antonio Eufrásio (2019)
Lectins are proteins that bind to carbohydrates or glycoconjugates, reversibly, without changing the structure of them. They can interact with the cell surface and promote the most diverse biological activities. Frutalin (FTL) is the most abundant lectin in breadfruit seeds (Artocarpus incisa), belonging to the jacalin-related lectin family (JRL). FTL specifically recognizes α-D-galactose and has been successfully used in immunobiological research for the recognition of cancer-associated oligosaccharides. Here, we report the full 3D structure of the FTL, as determined by X-ray crystallography. The crystals obtained were diffracted at 1.81 Å (Apo-frutalin) and 1.65 Å (FTL-D-Gal) resolution. The lectin exhibits post-translational cleavage producing an α- (133 amino acids) chain and a β chain (20 amino acids), exhibiting a homotetramer when in solution, with a typical β-prism present in the JRLs. The β-prism of the FTL is composed of three β-sheets forming three antiparallel Greek key motifs. The carbohydrate binding site (CBS) involves the N-terminus of the α-chain and is formed by four key residues: Gly25, Tyr146, Trp147 and Asp149. These results were used in simulations of molecular dynamics in aqueous solutions to clarify the molecular bases of glycan binding to CBS. The simulations suggest that the excision of the Thr-Ser-Ser-Asn peptide (TSSN) reduces the CBS rigidity of the FTL, increasing the number of interactions with ligands and resulting in multiple binding sites and anomeric recognition of the sugar molecules. Our findings provide a new perspective to further elucidate the FTL's versatility in many biological activities, including the recognition of blood serum glycoproteins that elicit neoplasms through their overexpression. The interaction of FTL with Complement-C3 glycoprotein was investigated by molecular docking simulations and the molecular bases of this recognition were observed, proving the involvement of CBS in ligand recognition.